Keterampilan Menulis Puisi dengan Penguatan Karakter Melalui Teknik Sanggam Riska - Supriyanto, Supriyanto (Jurnal Didaktika Pendidikan Dasar, 2023)
This article is based on good practice on how to integrate strengthening character education through the “Sanggam Riska” technique with the aim of improving poetry writing skills for grade VIII junior high school students. It was found that there were indications of a student’s lack of courtesy, both to fellow students and to the teacher. The "Sanggam Riska" technique is a technique of stimulating the image of the gathering of words in groups. Learning with the "Sanggam Riska" technique can significantly improve students’ ability to choose words, figure of speech, and rhyme in writing poetry for students at SMP N 1 Kemranjen which has implications for increasing literary learning achievement by strengthening character education. Strengthening character education in the form of cooperation in word contributions, patiently waiting for their turn, and self-confidence was clearly seen when students had group discussions.